Model free adaptive control : theory and applications - Hou, Zhongsheng (CRC Press, 2014)
This book summarizes theory and applications of model-free adaptive control (MFAC), which is a pure data-driven model-free control method, and whose controller design and stability analysis merely depend on the measured input and output data of the controlled plants. Topics include: pseudo partial derivative, pseudo gradient, pseudo Jacobian matrix, and generalized Lipschitz conditions, etc.; dynamic linearization approaches for nonlinear systems, such as compact-form dynamic linearization, partial-form dynamic linearization, and full-form dynamic linearization; a series of control system design methods, including MFAC prototype, model-free adaptive predictive control, model-free adaptive iterative learning control, and the corresponding stability analysis and typical applications in practice. The book provides results that are rigorously proved and accompanied by examples with numerical simulations or experiments. --